Islamic Education from the Perspective of KH Hasyim Asy'ari - Zian Salsabila Bidaula (ATTAQWA: Jurnal Pendidikan Islam dan Anak Usia Dini, 2024)
Hasyim Asy'ari as a Muslim intellectual, introduced the results of his thoughts on Islamic education as an aspect of life formed in the religious field. He implemented an education system based on the Qur'an as a guideline. This article aims to analyze the concept of Islamic education in the perspective of KH. Hasyim Ash'ari. This research is qualitative research in the form of literature study. The object of this study is the concept of KH thinking. Hasyim Asy'ari on Islamic education. The results showed that Islamic education in the perspective of KH. Hasyim Asy'ari is patterned on traditional Islam which emphasizes the values of Sufism which is divided into three areas, namely Sufism, theology and jurisprudence. This is very different from modernist ideas, until the works he wrote adhered to traditional Islamic beliefs.